Decorative elements on the exterior façade of the garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The jangha (wall) of the garbhagriha (sanctum sanctorum) has a broad floral scroll that runs across all three walls and divides the wall into upper and lower parts. On the side walls (north and south) jaali or checkered windows are added which are topped by double chaitya arches. The rear of the garbhagriha has no window but it depicts chaitya arches.